2003
DOI: 10.1016/s0006-3495(03)75012-7
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Membrane Interactions of Saposin C: In Situ Atomic Force Microscopic Study

Abstract: Saposin C (Sap C) is a small glycoprotein required for hydrolysis of glucosylceramidase in lysosomes. The full activity of glucosylceramidase requires the presence of both Sap C and acidic phospholipids. Interaction between Sap C and acidic phospholipid-containing membranes, a crucial step for enzyme activation, is not fully understood. In this study, the dynamic process of Sap C interaction with acidic phospholipid-containing membranes was investigated in aqueous buffer using atomic force microscopy. Sap C in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
1
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
5
23
1
1
Order By: Relevance
“…One model suggests that the reduced membrane thickness may be due to partial lipid removal from the top leaflet by saposin molecules 12 leaving an intact lower leaflet. The hydrophobic tails of lower acyl chains are shielded from the aqueous environment by amphiphilic saposin molecules, possibly in an open conformation that permits amphiphilic shielding.…”
Section: Mechanism Of Saposin Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…One model suggests that the reduced membrane thickness may be due to partial lipid removal from the top leaflet by saposin molecules 12 leaving an intact lower leaflet. The hydrophobic tails of lower acyl chains are shielded from the aqueous environment by amphiphilic saposin molecules, possibly in an open conformation that permits amphiphilic shielding.…”
Section: Mechanism Of Saposin Actionmentioning
confidence: 99%
“…Here, we present the direct visualization by atomic force microscopy (AFM) imaging of model lipid bilayers subjected to saposins A, B or C. Previous AFM imaging results have shown that saposin C has the potential of restructuring phospholipid membranes. [11][12][13] Focusing on saposin C, we demonstrate stable association of protein with transformed membranes using simultaneous AFM and fluorescence imaging. Finally, we address the solubilizer and liftase mechanisms by following the kinetics of membrane lipid markers subjected to saposin C.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Similarly, saposin, myelin, and cytochrome C all interact at least partially through electrostatic interactions with bilayers containing charged lipids. [10][11][12] This work provides information on the role of electrostatic and nonspecific interactions and membrane composition in controlling protein adsorption on lipid bilayers and also yields insight into protein-mediated membrane disruption. In order to provide more direct evidence for the interaction of synapsin with anionic membrane domains, we have used AFM and near-field scanning optical microscopy (NSOM) [19][20][21][22] to image supported lipid bilayers comprised of mixtures of neutral phosphatidylcholine (PC) and anionic PS lipids.…”
Section: Introductionmentioning
confidence: 99%
“…A general property of saposins is their lipid membrane binding activity (9) because they play important roles in lipid transport (10), lipid microdomain assembly (11), and reorganization of biological membranes (12)(13)(14). Specifically, saposin C associates with lipid membranes by embedding into membrane leaflets.…”
mentioning
confidence: 99%